Investigating the Challenges Faced by EFL Students in Translating Cooking Recipes - Hayati, Sifa; Nugraha, Richard Ferry; Norahmi, Maida; Utami, Imelda Putri; Munawarah, Siti (General English Education, 2025)
This study aims to investigate the challenges faced by EFL students in translating cooking recipes. It was conducted on sixth-semester students from class B in the translation course. The research employed a qualitative descriptive method with thematic analysis to identify and interpret key patterns within the data. Data collection was carried out through a triangulation approach, combining mixed-method questionnaires and semi-structured interviews. The findings revealed four main themes and one additional theme related to the students’ difficulties: (1) vocabulary-related challenges, (2) grammar and equivalence issues, (3) translation quality and self-confidence, (4) limited exposure and cultural context, and (5) translation methods and procedures as an additional theme. These challenges reflect the complexity of translating procedural texts, especially recipes, which often include culturally bound terms, specific measurements, and imperative instructions. The study concludes that translating recipes presents significant linguistic and contextual challenges for EFL students. It suggests the need for more targeted strategies and exposure to authentic materials in translation to help students improve their translation and overcome practical difficulties in translating specialized texts like recipes.